Melasma in the people of Sub-Himalayan region of Eastern India - Halder, Saswati; Halder, Atin; Nag, Subhas Ch.; Rajesh, Dr.; Sarkar, Prodip (Journal of Pakistan Association of Dermatologists, 2016)
Objective To determine the spectrum of the factors influencing melasma in the people of Sub-Himalayan region of Eastern India especially Mongoloid in origin (Nepalese). Â Patients and methods Hundred (94 females and 6 males) new cases of melasma, of Eastern part of sub-Himalayan region, were subjected to detail history taking regarding family, occupation, and daily activities. A thorough clinical evaluation followed by investigation was done. Â Results Fifty cases were in the age group of 21-30 years, whereas according to the onset of disease 54 cases were in that age group. Sixteen cases had the age of onset 11-20 years, of these 75% had positive family history. Overall family history was observed in 40% of cases. By occupation 70 cases were housewives and the duration of sun exposure was more than 2 hours in 80% of cases. Twenty two patients were oral contraceptive pill users and 6 cases were pregnant women. Â Conclusion The people suffering from melasma of Eastern sub-Himalayan region, have genetic predisposition especially in early onset disease. Quantum of UV exposure not only depends on the duration but also reflected sun light from snow covered hills. Sunscreen is used as preventive measure. Â